De Tian’anmen à Central : différentes batailles, un même combat - Lun Zhang (Socio, 2015)
From the Tiananmen Square Movement to the recent Occupy Central protests which emerged in Hong Kong, a vast socio-historical movement is taking shape in which the actors try to obtain and defend social and political rights as citizens, masters of their own destiny.